Microbial Bioprospecting for Sustainable Development (Springer Singapore, 2018)
This book presents a comprehensive overview of the use of microorganisms and microbial metabolites as a future sustainable basis of agricultural, environmental and industrial developments. It provides a holistic approach to the latest advances in the utilization of various microorganism bioprospecting including their wide range of applications, traditional uses, modern practices, and designing strategies to harness their potential. In addition, it highlights advanced microbial bioremediation approaches, including genetic manipulation, metagenomics analysis and bacteriophage-based sensors for the detection of food-borne pathogens. Lastly, it elaborates on the latest advances regarding the role of microbes in the sustainable development of various industrial products.